Properties of modified high permeable concrete with a crumb rubber - Ng C.Y.; Narong A.R.; Kamarul Zaman A.B.; Mustaffa Z.; Mohammed B.S.; Ean L.W. (Bentham Science Publishers, 2023)
Background: High permeable concrete is designed with high porosity, which allows water to pass through it. By considering this ability, it has been widely used for various applications including high permeable road pavement. However, to fully adopt highly permeable road pavement technology is challenging due to high cost and maintenance, besides the present engineers and contractors have insufficient expertise and experience with this technology. Henceforth, the high porosity property is highly favorable for road curb applications especially in the tropical region like Malaysia with high rainfall intensity. Objective: This paper aimed to determine the properties of the concrete experimentally, and propose the optimum mix design of high permeable concrete for road curb. Methods: The flow value and setting time of the cement paste were investigated. Next, the effects of the modified high permeable concrete with varying amount of crumb rubber on compressive strength, permeability and void ratio were also investigated. Results and Conclusion: Results have revealed that the workability of the cement paste increases when the water-binder ratio and the amount of fly ash increase. Meanwhile, an increasing amount of cement ratio and crumb rubber lowers the flow value and consequently leads to lower void ratio and permeability. Besides, it has been found that the higher the compressive strength, the lower the void ratio and permeability of the concrete. The research findings support that using an optimum amount of cement replacement with crumb rubber as an additive may increase the performance a high permeable concrete. Herein, the results indicate that the mix design of the concrete studied has the potential to be applied onto the road curb. 2019 Ng et al.